Status Of Mangrove and Mangrove Associate Medicinal Plants Atkokillai in Mullaithivu District and Conservation Strategy - Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
Medicinal plants are abundantly grown and found in mountainous places, forests, river valleys, coastal areas, Mangal areas and open plateaus in nature. The mangrove differs from environment to environment and from one country to another. Even though they are mostly found in places near saltwater, they are also found in places of muddy water and near to lagoons. The flora of Mangrove and Mangrove Associates medicinal plants of Kokillai lagoon area reserve was surveyed over a period of three months(March 2014 to May 2014) using a Belt Transects Method (50mx5m). The objective of the study was to determine the presence of potential mangroves and mangrove associate medicinal plants at kokillai in Mullaithivudistrict. The investigation revealed the presence of 4 species of mangroves and 20 species of mangrove associated medicinal plants belonging to 14 families. The documented medicinal plant grouping based on morphology revealed the existence of herbs (3) trees (12) climbers (4) and shrubs (5). A total of 24 species of Medicinal plants were recorded, this comprises perennials (21) and Annual - (3). One native medicinal plant was recorded namely Salvadorapersica(Tooth Bruch tree) and (2) poisonous plants were also recorded. Out of 24 mangrove and mangrove associate Medicinal plant, 8 used in rheumatism, 6 used for skin diseases, one for urinary disorder, one in Diabetic mellitus, one for used as spinach, 4 used for fracture of dislocation. The thirty years of war, displacement and associated pressure on mangroves for firewood, and Tsunami had collectively contributed to the destruction of the mangroves and mangrove associates largely in the Northern Province. These are considered as threats to mangrove and mangrove associate medicinal plants in studied area. As we move on to activate the propagation of the mangrove and mangrove associate medicinal plants in the mangal areas. We must take efforts to conserve the mangrove mangrove associate medicinal plants thus conserving their Medicinal value, and to preserve the ecosystem.
Keywords: Mangrove; Mangrove associate; medicinal plants; Kokillai